The Role of the Knowledge Intermediary in Evangelical Project and Production Management Theories - Jaydeep Balakrishnan (Journal of Engineering, Project, and Production Management, 2019)
Given the creation of different types of knowledge propositions in project and production management, we discuss what we call ‘evangelical’ propositions and what as knowledge intermediaries our role should be in its dissemination. We examine both proposition accuracy as well as the process by which the proposition was arrived at. We suggest strategies for knowledge intermediaries to adopt in order to achieve balance in evaluating these developments. Further, we support our suggestions by examining the development of the Theory of Constraints (TOC) and Critical Chain Project Management (CCPM) and the debate that has accompanied these, as a case study. The debate relates to how much of the knowledge proposition in these is really new and whether the method of developing the proposition was lacking in some sense. Knowledge intermediaries, those who are expected to play an important role in disseminating knowledge, will be better prepared to deal with similar innovations in a balanced manner, by analyzing the case of TOC/CCPM.